2018
DOI: 10.1002/anie.201710740
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo EPR Characterization of Semi‐Synthetic [FeFe] Hydrogenases

Abstract: EPR spectroscopy reveals the formation of two different semi‐synthetic hydrogenases in vivo. [FeFe] hydrogenases are metalloenzymes that catalyze the interconversion of molecular hydrogen and protons. The reaction is catalyzed by the H‐cluster, consisting of a canonical iron–sulfur cluster and an organometallic [2Fe] subsite. It was recently shown that the enzyme can be reconstituted with synthetic cofactors mimicking the composition of the [2Fe] subsite, resulting in semi‐synthetic hydrogenases. Herein, we em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
0
40
0
Order By: Relevance
“…To generate active hydrogenase in concentrations suitable for whole-cell spectroscopy, the HydA1 protein was heterologously expressed in BL21(DE3) E. coli cells, similar to previous reports. [44][45][46] The absence of the [FeFe]-hydrogenase specic maturation machinery in E. coli results in the synthesis of an inactive form of the enzyme containing the [4Fe-4S] H cluster but lacking the [2Fe] H subsite (apo-HydA1). 50 mL cell cultures were concentrated to 2 mL and depleted of O 2 at which point the synthetic cofactor mimic [2Fe] adt was added to the medium, and the H-cluster assembly monitored by EPR spectroscopy and H 2 production assays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To generate active hydrogenase in concentrations suitable for whole-cell spectroscopy, the HydA1 protein was heterologously expressed in BL21(DE3) E. coli cells, similar to previous reports. [44][45][46] The absence of the [FeFe]-hydrogenase specic maturation machinery in E. coli results in the synthesis of an inactive form of the enzyme containing the [4Fe-4S] H cluster but lacking the [2Fe] H subsite (apo-HydA1). 50 mL cell cultures were concentrated to 2 mL and depleted of O 2 at which point the synthetic cofactor mimic [2Fe] adt was added to the medium, and the H-cluster assembly monitored by EPR spectroscopy and H 2 production assays.…”
Section: Resultsmentioning
confidence: 99%
“…7,13,[41][42][43] We recently adopted this strategy for in vivo applications, enabling the preparation of fully functional, semisynthetic enzymes in both E. coli and cyanobacteria. 6,[44][45][46] Herein, we take advantage of this protocol to perform spectroscopic investigations of [FeFe]-hydrogenase in whole cells (Fig. 1).…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23] The well-studied [FeFe]hydrogenase from C. reinhardtii (Cr-HydA1) belonging to subclass M1 (sub-class nomenclature is derived from Meyer 20 and Calusinska et al 21 ) was included as a positive control as it has previously been shown to work under the presented in vivo conditions. 24,26 M1 is the structurally simplest known [FeFe]hydrogenase sub-class consisting only of the H-domain ( Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…24,25 Moreover, we have reported how the cofactor of the resulting semi-synthetic enzyme can be monitored in vivo by electron paramagnetic resonance (EPR). 26 Herein we present how the combination of articial maturation and biophysical characterization under in vivo conditions can be turned into a tool for efficient screening of novel [FeFe]hydrogenases. The method is applicable to a range of E. coli expression and growth conditions, and allows for basic characterization without the need for time-consuming protein purication.…”
Section: Introductionmentioning
confidence: 99%